2023
DOI: 10.3389/fcimb.2023.1190859
|View full text |Cite
|
Sign up to set email alerts
|

Lactonase-mediated inhibition of quorum sensing largely alters phenotypes, proteome, and antimicrobial activities in Burkholderia thailandensis E264

Abstract: IntroductionBurkholderia thailandensis is a study model for Burkholderia pseudomallei, a highly virulent pathogen, known to be the causative agent of melioidosis and a potential bioterrorism agent. These two bacteria use an (acyl-homoserine lactone) AHL-mediated quorum sensing (QS) system to regulate different behaviors including biofilm formation, secondary metabolite productions, and motility.MethodsUsing an enzyme-based quorum quenching (QQ) strategy, with the lactonase SsoPox having the best activity on B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Transcriptomic and proteomic studies showed that around 6% and 3% in P. aeruginosa and 9% and 18% in B. thailandensis, respectively, are impacted. Similarly, the expression of 12% of the V. campbellii transcriptome is modified upon QS, affecting many cellular functions (e.g., primary metabolism, motility, secretion systems). ,, Among these important changes, modulations in the synthesis of secondary metabolites have been identified. Bacteria live in communities in conditions where nutrients can be scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomic and proteomic studies showed that around 6% and 3% in P. aeruginosa and 9% and 18% in B. thailandensis, respectively, are impacted. Similarly, the expression of 12% of the V. campbellii transcriptome is modified upon QS, affecting many cellular functions (e.g., primary metabolism, motility, secretion systems). ,, Among these important changes, modulations in the synthesis of secondary metabolites have been identified. Bacteria live in communities in conditions where nutrients can be scarce.…”
Section: Discussionmentioning
confidence: 99%
“… Bactobolin was identified because of its antimicrobial activity against a broad range of bacteria including Bacillus subtilis , , Bacillus cereus , Chromobacterium violaceum , Staphylococcus aureus , and Escherichia coli and antifungal activity against Candida krusei. Bactobolin inhibits protein synthesis by binding to the 50S ribosomal subunit in proximity to the L2 protein. , Besides its antimicrobial effects, 1 was reported to have antitumor activity in vitro on different cell types , and in vivo in murine models. , A recent study demonstrated that the disruption of QS considerably altered the proteome of B. thailandensis E264, including the biosynthesis of bactobolin molecules, as well as various secondary metabolites such as 4-hydroxy-3-methyl-2-alkenylquinoline (HMAQ; 2 ) and its derivatives, whose production was considerably impacted …”
Section: Introductionmentioning
confidence: 99%